2004
DOI: 10.21273/hortsci.39.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Scheduling of Kohlrabi (Brassica oleracea var. gongylodes) Using Crop Water Stress Index

Abstract: Two-year field experiments were carried out to evaluate the suitability of crop water stress index (CWSI) as a basis for irrigation scheduling of kohlrabi (Brassica oleracea L. var. gongylodes) by comparison with irrigation scheduling based on total soil water content (SWC). In the first year, irrigation scheduling when CWSI exceeded 0.3 resulted in more frequent water applications, but the total amount of irrigation water given was lower compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…In the previous studies carried out was reported CWSI values give crucial information about the water stress experienced by plants. It has been pointed out that with irrigation schedules to be determined by taking these outcomes into account, it is possible to increase the yield, quality and water saving (Idso et al 1981 ; Reginato 1983 ; Sepaskhah and Kashefipour 1994 ; Olufayo et al 1996 ; Cárcova et al 1998 ; Alderfasi and Nielsen 2001 ; Cremona et al 2004 ; Yuan et al 2004 ). Köksal and Yıldırım ( 2011 ) stated that the CWSI can be used effectively in the irrigation scheduling of sugar beet, under semi-arid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies carried out was reported CWSI values give crucial information about the water stress experienced by plants. It has been pointed out that with irrigation schedules to be determined by taking these outcomes into account, it is possible to increase the yield, quality and water saving (Idso et al 1981 ; Reginato 1983 ; Sepaskhah and Kashefipour 1994 ; Olufayo et al 1996 ; Cárcova et al 1998 ; Alderfasi and Nielsen 2001 ; Cremona et al 2004 ; Yuan et al 2004 ). Köksal and Yıldırım ( 2011 ) stated that the CWSI can be used effectively in the irrigation scheduling of sugar beet, under semi-arid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that applied irrigation water decreased by 25% (Mathew and Senthilvel, 2004). Cremona et al (2004) evaluated two methods of farm irrigation scheduling, one based on measuring plant stress index (canopy temperature) and the other based on measuring soil moisture. They con-cluded that by measuring canopy temperature, the water productivity increases by 25%.…”
Section: Introductionmentioning
confidence: 99%
“…엽온은 낮에는 일사와 기온에 따라 높아 지며, 바람과 증산작용에 의해 잎의 수분이 증발하여 엽온이 떨어진다 (Kim et al, 1999). Idso(1977) Alderfasi and Nielsen(2001), Cremona et al(2004), Erdem et al(2010) 에 의해 계속되고 있다. 국내에서도 근적외선 온도계로 엽온을 비접촉식으로 측정하여 작물의 온도 변화에 따른 수분스트레스 지수에 관한 연구 (Kim et al, 1999, Lee andLee, 2001)…”
unclassified